Genotypic and tissue-specific variation of Populus nigra transcriptome profiles in response to drought - Christian Eckert; Henning Wildhagen; Maria João Paulo; Simone Scalabrin; Johannes Ballauff; Sabine K. Schnabel; Vera Vendramin; Joost J. B. Keurentjes; Marie-Béatrice Bogeat-Triboulot; Gail Taylor; Andrea Polle (Scientific Data, 2022)
Measurement(s) transcriptome Technology Type(s) illumina sequencing Factor Type(s) treatment Sample Characteristic - Organism Populus nigra Sample Characteristic - Environment greenhouse experiment